Navigating the politics and processes of food systems transformation: Guidance from a holistic framework - Béné, Christophe; Abdulai, Abdul-Rahim (Frontiers Media, 2024)
The call for transforming food systems from their current unsustainable trajectories toward more desirable, healthy, sustainable, resilient, and equitable outcomes has received unprecedented echoes recently—particularly following the 2021 UN Food Systems Summit. But lack of guidance on how to do so in a comprehensive and integrated manner has left many actors uncertain, skeptical, or even low-spirited about the prospects of delivering such an ambitious task. Through this work, we argue that food systems transformation is not an impossible goal to aspire for; however, whether we achieve any form of transformation is essentially down to how food systems politics are enacted. Politics, we posit, is at the center of creating and maintaining current unsustainable food system trajectories and will also be crucial in guiding change processes toward sustainable goals. In this paper, we explore this argument through a conceptual framework. The framework, which is relevant for both high and lower-income countries, integrates multiple perspectives and practical experiences on transition, transformation and politics to propose a holistic diagnostic and prescriptive tool for food systems transformation. Three critical lessons emerge from this: first, the transformation (of food systems) must be normative, deliberate and goal-oriented—as opposed to driven by technological innovations; second, the process must account for, integrate, and build on the multi-dimensional and multi-procedural nature of the politics that drive (or resist) changes; and third, the transformation needs to build on a strong driving environment, one that transforms not just food systems but also their governance.